Seasonal variations in air concentrations of 27 organochlorine pesticides (OCPs) and 25 current-use pesticides (CUPs) across three agricultural areas of South Africa - Veludo, Adriana Fernandes; Martins Figueiredo, Daniel; Degrendele, Céline; Masinyana, Lindile; Curchod, Lou; Kohoutek, Jiří; Kukučka, Petr; Martiník, Jakub; Přibylová, Petra; Klánová, Jana; Dalvie, Mohamed Aqiel; Röösli, Martin; et al. (Chemosphere, 2022)
For decades pesticides have been used in agriculture, however, the occurrence of legacy organochlorine pesticides (OCPs) and current-use pesticides (CUPs) is poorly understood in Africa. This study investigates air concentrations of OCPs and CUPs in three South African agricultural areas, their spatial/seasonal variations and mixture profiles. Between 2017 and 2018, 54 polyurethane foam-disks passive air-samplers (PUF-PAS) were positioned in three agricultural areas of the Western Cape, producing mainly apples, table grapes and wheat. Within areas, 25 CUPs were measured at two sites (farm and village), and 27 OCPs at one site (farm). Kruskal-Wallis tests investigated area differences in OCPs concentrations, and linear mixed-effect models studied differences in CUPs concentrations between areas, sites and sampling rounds. In total, 20 OCPs and 16 CUPs were detected. A median of 16 OCPs and 10 CUPs were detected per sample, making a total of 11 OCPs and 24 CUPs combinations. Eight OCPs (trans-chlordane, o,p'-/p,p'-dichlorodiphenyldichloroethylene (DDE)/dichlorodiphenyltrichloroethane (DDT), endosulfan sulfate, γ-hexachlorocyclohexane and mirex) and two CUPs (carbaryl and chlorpyrifos) were quantified in all samples. p,p'-DDE (median 0.14 ng/m3) and chlorpyrifos (median 0.70 ng/m3) showed the highest concentrations throughout the study. Several OCPs and CUPs showed different concentrations between areas and seasons, although CUPs concentrations did not differ between sites. OCPs ratios suggest ongoing chlordane use in the region, while DDT and endosulfan contamination result from past-use. Our study revealed spatial and seasonal variations of different OCPs and CUPs combinations detected in air. Further studies are needed to investigate the potential cumulative or synergistic risks of the detected pesticides.
Keywords: Organochlorine pesticides; Pesticide mixtures; pesticidy; Passive air-sampling; chlorované uhlovodíky; Western cape; Environmental Monitoring; Hydrocarbons, Chlorinated; Agriculture; Air Pollutants; Pesticides; Current-use pesticides; Seasonal variations; látky znečišťující vzduch; monitorování životního prostředí; roční období; zemědělství; South Africa; Seasons; Jihoafrická republika